Effectiveness of Mental Immunization Program Training on Social Competency and Personality Traits of Individuals With Cerebral Palsy - Mohammad Ashoori; Masoume Pourmohamadreza-Tajrishi; Seyyedeh Somayyeh Jalil-Abkenar; Ali Mohammad Fallah; Samad Azimi Garoosi (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Most children and adults with cerebral palsy do not have appropriate social competency and personality traits, which  in turn leads to psychological problems in their life and negatively affects their interactions. The purpose of the present research was to investigate the effectiveness of mental immunization program training on social competency and personality traits of individuals with cerebral palsy in Tehran city. Materials & Methods The present research had a semi-experimental study with pretest and posttest design and control group. The study population included adolescents with cerebral palsy in the age group of 12-16 years in the academic year 2015-2016. Subjects were selected with the help of the convenient sampling method. In this study, 34 adolescents with cerebral palsy participated. They belonged to the middle socio-economical class. The subjects were randomly divided into experimental and control group, each of which consisted of 17 adolescents.  The experimental group received psychological immunization program training across 10 sessions (45 minutes for per session; twice a week) while control group did not receive any training. The instruments of present research were social competency questionnaire of Felner, Lease and Philips and big five factor personality inventory (NEO-FFI) of Costa and McCrae. The obtained data were analyzed by using mean, standard deviation and multivariate analysis of covariance (MANCOVA) test with the 21st version of the statistical package for social sciences (SPSS). Results The normality of variables and contingency of variance and covariance assumptions were tested. The Kolmogorov Smirnov test showed that all variables were normal (P>0.05). The Box test confirmed contingency of variance-covariance assumption (P=0.28). Therefore, assumptions of MANCOVA test were confirmed and were used the MANCOVA test for analysis of data. The findings of this research showed that there was a significant increase in social competency mean scores of experimental group post intervention in comparison with control group (P<0.001). Also, personality traits mean scores of experimental group was significantly in  neuroticism, extroversion, agreeableness and conscientiousness subscales (P<0.05). In other words, mental immunization program training had a significant effect on these subscales but not on openness (P>0.05). Conclusion The results of the present research indicated a significant increase in social competency in adolescents with cerebral palsy. Also, desirable changes were found to be developed in the personality traits of these adolescents. In other words, there was a decreased level of neuroticism and significant increase in positive traits such as extroversion, agreeableness and conscientiousness. The overall results of the present research indicated that mental immunization program training led to improvement in social competency and personality traits of individuals with cerebral palsy. Therefore, paying attention to the mental immunization program training is essential, and planning for providing of psychological immunization program training is of particular importance. Cerebral palsy affects all aspect of an individual’s life and implementing the mental immunization program training has been associated with effective outcomes. Therefore, instructional interventions such as mental immunization program training are required . While a lot of research works have been conducted with regard to the effectiveness of mental immunization program training on social competency and personality traits of normal students, only a few investigations have been carried out for the same in relation to individuals with cerebral palsy. As far as present study used experimental method, could be cautioned in generalization of results . Another limitation of this study is the use of self-reporting questionnaires, wherein individuals do not feel the responsibility to answer correctly and honestly in order to avoid stigma or rejection by the community. It is recommended that the psychological immunization program training, which is very helpful in the instruction  of teenagers with cerebral palsy, be used in primary schools and among various categories of exceptional students.